The Implementation of Inquiry-Based Learning for Teaching English at SMP Muhammadiyah 4 Sambi in 2015/2016 Academic Year - Erawati, Menik; , Prof. Dr. Endang Fauziati, M.Hum; , Mauly Halwat Hikmat, S.Pd., M. Hum.,Ph.D (2016)
The objective of this study is to describe the implementation of Inquiry-based Learning for teaching English at SMP Muhammadiyah 4 Sambi in 2015/2016 academic year that consisted of 1) Learning objectives, 2) Classroom procedures, 3) Classroom techniques, 4) The roles of instructional material, 5) Teacher roles, 6) Student roles, 7) Media, 8) Types of assessment. This research is descriptive qualitative research. The researcher gets the data from event, informant, and document. The subject of this study are English teacher of seventh grade students and the students of seventh grade at SMP Muhammadiyah 4 Sambi. The method of collecting data are observation, interview, and document. The analyzing data are reducing data, displaying the data, and drawing conclusion. The result of the study are: 1) There are two learning objectives namely, general learning objectives and specific learning objectives. 2) Classroom procedures used is pre-teaching, while-teaching (Exploration, Elaboration, Confirmation), and post-teaching. 3) Classroom techniques used is brainstorming, oral repetition, answering-question, role-play, comprehension, free writing, and summarizing. 4) The instructional material used are printed and non-printed material. The roles of instructional material were: a) as a source of activities for learner practice and communicative interaction; b) as a source of stimulation and ideas for classroom language activities; and c) as a reference source for learners on grammar, vocabulary, pronunciation. 5) Teacher roles are as planner, manager, quality controller, group organizer, facilitator, and motivator. 6) Student role are as learner, subject of learning, members, tutor, performer, and monitor and evaluator of his or her own progress. 7)The media used in teaching learning process is pictures and images, the Overhead Projector (OHPs), board, and realia. 8) Assessment tools used are test such as: daily test, midterm examination, and final examinations and non-test such as: listen and repeat, responsive in the question-answers from the teacher, interactive in the conversation performance, reading outcomes, writing outcomes to evaluate the students.